Chemical variables - lake from Erssjön, Floating platform, 2016-05-10–2018-05-15 - Skogaryd Research Catchment (University of Gothenburg, 2026)
Manual grab samples for chemical analysis are taken from the lake on a biweekly basis during ice-free conditions, and on a monthly basis during ice cover conditions. At the central lake sampling location water samples are collected from both epi- and hypolimnion during periods of stratification.
Skogaryd Research Catchment (2026). Chemical variables - lake from Erssjön, Floating platform, 2016-05-10–2018-05-15 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/HYBsAawdpW-PBZC01y5nkHfD
Keywords: Skogaryd Research Catchment; Lake; Time instant; Time instant; Water temperature; Water temperature; pH; pH; Electrical conductivity; Electrical conductivity; Dissolved organic carbon; Dissolved organic carbon; Total nitrogen; Total nitrogen; Phosphate-P; Phosphate-P; Ammonium-N; Ammonium-N; Nitrate-N; Nitrate-N; Fluorine; Fluorine; Chlorine; Chlorine; Sulphate-S; Sulphate-S; Aluminium; Aluminium; Arsenic; Arsenic; Boron; Boron; Barium; Barium; Beryllium; Beryllium; Bismuth; Bismuth; Calcium; Calcium; Cadmium; Cadmium; Cobalt; Cobalt; Chromium; Chromium; Caesium; Caesium; Copper; Copper; Iron; Iron; Gallium; Gallium; Potassium; Potassium; Lithium; Lithium; Magnesium; Magnesium; Manganese; Manganese; Sodium; Sodium; Nickel; Nickel; Phosphorus; Phosphorus; Lead; Lead; Rubidium; Rubidium; Sulfur; Sulfur; Selenium; Selenium; Silicon; Silicon; Tellurium; Tellurium; Thallium; Thallium; Vanadium; Vanadium; Zinc; Zinc; Absorbance; Absorbance; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap